Comparative study of using rotation influence lines and their derivatives for structural damage detection. (February 2023) - Nady, Hazem O.; Abdo, Mohamed A.B.; Kaiser, Fayez
Abstract: Structural damage detection has recently become one of the most important topics for engineering structures due to its benefits in enhancing safety, reducing life-cycle cost and providing guidance for system construction and maintenance. This research studies the accuracy of using rotation influence lines (RIL) and their derivatives (first and second derivatives) for detecting structural damage characteristics (location and severity). The study includes an analytical investigation of damage detection of multiple damages in simply supported beam. Then, numerical studies have been conducted to investigate the effectiveness of the proposed method for damage identification of simply supported beam (determinate structure), continuous beam (indeterminate structure) with different damage characteristics. Furthermore, the most effective inclinometer locations and number of inclinometers for structural damage detection on simply supported and continuous beams are reported. Furthermore, noise intensity effects from the limited inclinometer precision, inclinometer faults and transmission errors are discussed in this paper.